PERANCANGAN RUAS JALAN AKSES KE TERMINAL PETI KEMAS PELABUHAN TANJUNG EMAS - Riantaka Kosasih; Mu’adz Abdurrahman; Bambang Riyanto; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2016)
Pelindo III in 2015 was to improve the infrastructure in the port of Tanjung Emas in order to enhance the activities of loading and unloading of goods export import, as appropriate based RIP (Port Master Plan) Tanjung Emas Semarang in 2030, as well as to support ARTG. RIP in accordance with the construction of road access to the container terminal is a top priority for improving the infrastructure in ports of Tanjung Emas. Segment planned access road will have to be in the area of container terminal. Planning the access road to the container terminal is planned by the method of Britsh Standard and Highways with a path length of 925 m, which starts from STA 0 + 000 who are on the road coster port of Tanjung Emas and ends at STA 0 + 925 is the area CY1 (Countainer Yard 1) container terminal. Planned traffic lanes 2 lanes one way, without the median, without the shoulder of the road, a width of the road 10 m, side channel 1 m, with a design speed of 60 km/h.